2007
DOI: 10.1177/00222194070400050301
|View full text |Cite
|
Sign up to set email alerts
|

Language Delays, Reading Delays, and Learning Difficulties

Abstract: Researchers have hypothesized four levels of instructional dialogue and claimed that teachers can improve children's language development by incorporating these dialogue levels in their classrooms. It has also been hypothesized that enhancing children's early language development enhances children's later reading development. This quasi-experimental research study investigated both of these hypotheses using a collaborative service delivery model for Grade 1 children with language difficulties from a socially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…Further, since many of the interventions reviewed also included re-reading of texts (a fluency building activity) as a central element, our findings also suggest the utility of including fluency-building elements in interventions aimed at improving reading comprehension. This is aligned with research suggesting that multifaceted interventions that incorporate the teaching of a variety of reading-related skills are more effective than those that target only one skill [70,71]. Future research could investigate oral reading fluency interventions in comparison to interventions directly targeting reading comprehension for both fluency and reading comprehension outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Further, since many of the interventions reviewed also included re-reading of texts (a fluency building activity) as a central element, our findings also suggest the utility of including fluency-building elements in interventions aimed at improving reading comprehension. This is aligned with research suggesting that multifaceted interventions that incorporate the teaching of a variety of reading-related skills are more effective than those that target only one skill [70,71]. Future research could investigate oral reading fluency interventions in comparison to interventions directly targeting reading comprehension for both fluency and reading comprehension outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…The findings of this study are in accordance with those in the literature regarding different age groups. As has been previously mentioned, international studies using the PLAI-2 have demonstrated that the test is sensitive and has a positive predictive value for identifying changes in spoken language [9,10,12]. …”
Section: Discussionmentioning
confidence: 99%
“…This instrument can also serve as a control for language intervention programs for preschoolers [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, . (Hay, Elias, Fielding-Barnsley, Homel, & Freiberg, 2007;Ruan, Georgiou, Song, Li, & Shu, 2018). , Erika, 2001).…”
mentioning
confidence: 99%